Application of Active Cycle Breathing Technique (ACBT) Exercises on Hemodynamic Status in Pulmonary Tuberculosis Patients With Respiratory Problems : A Case Study - Indra Frana Jaya KK; Hili Auliana; Anggraini Dwika Damayanti; Angel Putri; Maya Susanti; Titi Hidayati; Yuri Mariza; Santi Herliza (Lentera Perawat, 2025)
Tuberculosis is an disease caused by the bacterium Mycobacterium tuberculosis and is a major public health problem in the world. One of the symptoms that arise from someone suffering from tuberculosis is hemodynamic disorders, especially respiratory pattern disorders. Objective: This study aims to describe the application of Active Cycle Breathing Technique (ACBT) training to hemodynamic status in pulmonary tuberculosis patients with problems with respiratory patterns at Siti Fatimah Regional Hospital, South Sumatra Province. Method: This study used a descriptive design with a case study approach on three pulmonary tuberculosis patients who experienced respiratory pattern disorders. The data obtained was analyzed by comparing respiratory patterns, hemodynamic status and Modified Medical Research Council (MMRC) scores before and after intervention. Results: The third patient showed a stable hemodynamic status and a decrease in respiratory pattern disturbances from dyspnea to prone to eupnea. This was seen from a decrease in the MMRC score of one grade in each patient after being given ACBT training. Conclusion: ACBT training is an intervention that can be used to improve hemodynamic status in pulmonary tuberculosis patients with problems with respiratory patterns. Suggestion: Nurses can include ACBT training intervention as a complementary therapy for freezing and it is hoped that further research can add sessions in ACBT training and with a larger sample.